Cardiovascular risk factors in mild adrenal autonomous cortisol secretion in a Caucasian population. Issue 9 (4th August 2022) - Adamska, Agnieszka; Ulychnyi, Vitalii; Siewko, Katarzyna; Popławska-Kita, Anna; Szelachowska, Małgorzata; Adamski, Marcin; Buczyńska, Angelika; Krętowski, Adam Jacek
Abstract : Cardiovascular risk factors could be present in mild adrenal autonomous cortisol secretion (MACS). However, the most frequent cardiovascular risk factors in MACS have not been established. The aim of the presseent study was to analyse the difference in cardiovascular risk factors in patients with MACS in comparison to those with non-functioning adrenal tumour (NFAT). A total of 295 patients with adrenal incidentaloma were included in this retrospective study. We divided our group into those who showed suppression in 1 mg overnight dexamethasone suppression test (DST) (NFAT) (serum cortisol level ≤1.8 μg/dL) and those who did not show suppression in the DST (MACS) (serum concentration of cortisol > 1.8 μg/dL and ≤5 μg/dL). In the studied groups, we analysed the presence of cardiovascular risk factors, such as obesity, prediabetes, type 2 diabetes mellitus (T2DM), hypertension, hyperlipidaemia, chronic kidney disease and cardiovascular events. In our study, 18.9% of patients were defined as MACS. Importantly, T2DM was diagnosed in 41% of MACS vs 23% of NFAT ( P  < 0.01) and higher frequency of occurrence of hyperlipidaemia in NFAT (72.4%) vs MACS (53.6%) ( P  = 0.01) was observed. We did not observed differences in the frequency of obesity, hypertension, chronic kidney disease, prediabetes, atrial fibrillation, stroke, ST and non-ST elevation myocardial infarction and coronary angioplasty between patients with MACS and NFAT (all P  > 0.05; respectively). In MACS, T2DM is more prevalent than in NFAT; hyperlipidaemia is more prevalent in NFAT. Accordingly, no differences were found in the incidence of obesity, hypertension, prediabetes, chronic kidney disease between studied groups as well as cardiovascular events.